Kissing canines associated with dentigerous cyst, a case report of transmigrated bilateral impacted mandibular canines - Ashok Dongol; Pradeep Acharya; Ram Prasad Yadav; Arun Kumar Mahat; Anjani Kumar Yadav; Ashish Shrestha6; Mehul Rajesh Jaisani (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2017)
Transmigration, a phenomenon most often involving mandibular canine, refers to the migration of an unerupted tooth from its normal position to the contralateral side. Bilateral mandibular canine impaction with transmigration is a rare occurrence. These canines may exhibit kissing phenomenon in the radiograph. Very few cases of bilaterally impacted canines associated with dentigerous cyst have been reported. The case reported here deals with the management of kissing canines associated with dentigerous cyst.